The Importance Of Three-Stage Model In Developing The Functional Status Of Athletes - Sabirova Nasiba Rasulovna (Research Parks Publishers, 2021)
The problem of improving the effectiveness of the Athlete Training Management System is that all stages of the multi-year process of sports training are considered in terms of training tools and methods